Acute Mastoiditis in the Pneumococcal Conjugate Vaccines Era. (2nd September 2014) - Tamir, Sharon‐Ovnat; Roth, Yehudah; Dalal, Ilan; Goldfarb, Abraham; Marom, Tal
Abstract : Objectives: (1) Describe the changing trends in mastoiditis incidence and bacteriology in the pneumococcal conjugate vaccine (PCV) era. Methods: PCV‐7 and PCV‐13 have been gradually implemented in the Israeli national immunization program in 2009 and 2010, respectively. We retrospectively identified children aged 0‐6 years who had middle ear cultures obtained from "severe" acute otitis media (AOM) episodes, defined as AOM requiring tympanocentesis or presenting with spontaneous otorrhea, during the years 2008‐2013. Of those, we identified children with acute mastoiditis. Data were extracted for demographic, clinical and microbial information. Results: Data from 295 eligible AOM episodes reported in 279 children were collected. Of those, 56 children with 57 episodes of acute mastoiditis were identified. Of these 36 were boys (64%) and 37 (66%) were <2 years old. During the pre‐PCV and the PCV introduction period (January 2008‐November 2010), mastoiditis incidence rate was significantly higher than the post‐PCV introduction era (December 2010‐December 2013) incidence, 0.23 versus 0.16/"severe" AOM episode, respectively ( P =. 04). Mastoiditis developed despite adequate systemic antibiotic therapy for AOM in 28 (49%) patients. Of the 21 (37%) positive cultures, Streptococcus pneumonia e was the most common bacteria, which was solely isolated in 17 (81%) episodes and in combination of Haemophilus influenzae in 1 (5%) episode. Notably, there were no isolates of S pneumoniae from mastoiditis patients following the first year after PCV‐13 introduction. Conclusions: Mastoiditis incidence complicating "severe" AOM decreased after the introduction of PCVs, which can be directly attributed to their effectiveness in reducing pneumococcal‐related AOM burden and complications.